Mrs. Orwell - Chalupa, Andrea, 1982- (23rd St., 2026)
"Eileen Blair, wife and partner of George Orwell, is brought out of her husband's shadow in this riveting graphic novel, which follows the couples' tireless campaign to expose difficult political truths through art."--Amazon.